The value proposition - Donaldson, Bill (Henry Stewart Talks, 2010)
What is value?, Definitions of value, The basic elements of value, The strategic dimensions of value, The economic dimensions of value, The behavioural dimensions of value, Starting from basics, STP marketing, Identify and select customers, Customer acquisition information, Select your value drivers, Score your attractiveness, Price competitiveness, Drivers of customer value, Reassess your value, Decide the value proposition, Communicate the proposition, Concluding factors